Rising challenges in periprosthetic joint infections: a focus on rare pathogens and their clinical implications - Lyu, Jianhua; Huang, Jiagu; Huang, Jiexin; Hu, Hongxin; Wang, Qijin; Ding, Haiqi; Li, Hongyan; Fang, Xinyu; Zhang, Wenming (Frontiers in Cellular and Infection Microbiology, 2024)
ObjectivesThe study aimed to evaluate differences in clinical characteristics and treatment outcomes of periprosthetic joint infection (PJI) attributed to rare versus common pathogens.MethodsData on PJI patients who underwent hip or knee arthroplasty at our center from April 2013 to December 2022 were retrospectively collected. Among the 219 enrolled patients, we compared 32 cases of PJI caused by rare pathogens with 187 controls of PJI caused by common pathogens, analyzing demographic information, clinical characteristics, and treatment outcomes.ResultsIn demographic data, the Charlson comorbidity index and preoperative invasive procedures were identified as risk factors for rare pathogen PJI. Clinically, the rare pathogen cohort exhibited a significantly higher rate of sinus tract formation compared to those with common bacteria PJI. In terms of laboratory findings, the mean serum C-reactive protein (CRP) was significantly lower in the rare pathogen group. This cohort also had a significantly lower culture positivity rate and a higher rate of polymicrobial co-infections. The median hospital stay was statistically longer for rare pathogen PJI cases than for those with common bacteria PJI. Furthermore, the rare pathogen group required longer antibiotic treatments and had higher rates of antibiotic-related adverse events, although reinfection rates did not significantly differ.ConclusionPJI caused by rare pathogens exhibits distinct clinical presentations. With advances in diagnostic techniques such as metagenomic next-generation sequencing (mNGS), optimized culture methods, and an interdisciplinary approach facilitating early targeted treatment, rare pathogen PJIs may achieve outcomes comparable to those of typical cases.